Low clonal propagation in Atlantic and Mediterranean populations of the red gorgonian Paramuricea clavata (Octocorallia) - Pilczynska, Joanna (2018)
Clonal propagation is a common feature of benthic marine organisms. In the present study, we investigated the contribution of clonal reproduction in the red gorgonian Paramuricea clavata. Mediterranean populations of P. clavata were severely affected by mass mortality events caused by increased water temperature in 1999 and 2003. The populations are characterized by slow growth and episodic recruitment, but after the observed mortalities, an unexpectedly high recovery rate was observed in the severely affected populations from the Ligurian Sea, NW Mediterranean. Ten years after the last mortality event, we investigated the contribution of clonal propagation in populations from the Ligurian Sea, where some populations were highly affected by mass mortality events, and from the Atlantic, where mortality was never observed. All individuals were genotyped for nine microsatellite loci. The contribution of clonal reproduction varied from 0% to 13% and did not differ significantly between affected and unaffected populations. We confirm by using genetic markers that clonal propagation in P. clavata is not common, and that the contribution of clones is too low to play an important role in red gorgonian reproduction and cannot contribute to population recovery at sites that have been affected by mass mortality events.